2022
DOI: 10.52768/2766-7820/1782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating plasma assisted noninvasive surgery (PANIS) as a new method for pterygium removal; a clinical case series

Abstract: Purpose: The present study aimed to evaluate the outcomes of a new technique for pterygium surgery using a plasma-based method. Methods: A clinical case series study was carried out in 6 patients. Six eyes with grade 2 or 3 of primary pterygium were operated. The pterygium head was detached from the corneal surface. Then, the free conjunctival edges were attached near the limbus using the plasma spots [generated by Plexr device (GMV, Rocca Priora, RM, Italy)]. Refractive Error (RE), Visual Acuity (VA), Intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In another research, Inflammatory cytokines in tear and serum has checked 4 times within 6 months follow-up after plasma spots on Rats conjunctiva, and this study also reported no persistent inflammatory responses [29]. After 3 animal studies, human ocular surface diseases have been targeted to treating with atmospheric low-temperature plasma and published case series studies, including conjunctivochalasis, conjunctival cyst, pinguecula, pterygium, punctal occlusion, conjunctival concretion, pseudophakic bullous keratopathy, conjunctival nevus [15,[30][31][32][33][34]. All these novel modalities have been taught to ophthalmologists all over the world, as a safe, office-based and effective approaches [35].…”
Section: Resultsmentioning
confidence: 76%
“…In another research, Inflammatory cytokines in tear and serum has checked 4 times within 6 months follow-up after plasma spots on Rats conjunctiva, and this study also reported no persistent inflammatory responses [29]. After 3 animal studies, human ocular surface diseases have been targeted to treating with atmospheric low-temperature plasma and published case series studies, including conjunctivochalasis, conjunctival cyst, pinguecula, pterygium, punctal occlusion, conjunctival concretion, pseudophakic bullous keratopathy, conjunctival nevus [15,[30][31][32][33][34]. All these novel modalities have been taught to ophthalmologists all over the world, as a safe, office-based and effective approaches [35].…”
Section: Resultsmentioning
confidence: 76%
“…These safety evaluations confirmed the initiation of human trials to use plasma technology for treating ocular surface diseases such as conjunctival cyst, conjunctivochalasis, pinguecula, pseudophakic bullous keratopathy, conjunctival concretion, pterygium, dry eye disease, and conjunctival nevus. A published case series about the PANIS modality (plasma-assisted noninvasive surgery) with an average follow-up of 6 months proved the safety and efficacy of this novel technique for treating common ocular surface diseases [7,[25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 98%
“…The PANIS method has been used to treat ocular surface diseases such as conjunctivochalasis, conjunctival cysts, dry eye disease, pinguecula, conjunctival concretion, pseudophakic bullous keratopathy, pterygium, and conjunctival nevus [36][37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%